(BeDABCO)2Pd2Cl6 (1‐benzyl‐4‐aza‐1‐azoniabicyclo[2.2.2]octane chloride) as a highly active catalytic system for the Stille cross‐coupling reaction under microwave irradiation. (27th March 2013) - Hajipour, Abdol R.; Najafi, Narges; Rafiee, Fatemeh
Abstract : An efficient catalytic system using (BeDABCO)2 Pd2 Cl6 was developed for the Stille cross‐coupling reaction. The substituted biaryls were produced in excellent yields in short reaction times using a catalytic amount of this catalyst in DMF at 120 °C. The ionic character of homogeneous catalyst and microwave irradiation and also DMF as microwave‐active polar solvent gave higher yields and shorter reaction times than conventional heating. Benzyl DABCO as an efficient ligand and also a quaternary ammonium salt had an efficient stabilizing effect on the Pd(0) species. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : A palladium catalyst is synthesized using N ‐benzyl DABCO chloride and palladium chloride and the efficiency of this catalytic system is evaluated for Stille reaction.